Promotion Strategy to Increase Sales Volume at Desi Store in Nagari Pinaga Aua Kuniang, Pasaman District, West Pasaman Regency - Yaumil Azizah; Rini Elvira; Faisal Hidayat; Zuwardi Zuwardi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine how to increase sales volume at Desi Store through promotional strategies. This study aims to formulate promotional strategies as an effort to increase sales volume at Desi Store which requires business actors to be honest, fair and responsible, understand the rules of trading according to sharia, conduct buying and selling based on divinity because Muslim sellers believe that all forms of transactions they make will be held accountable by Allah SWT. Desi Store is located in Nagari Pinaga, Aua Kuniang, Pasaman District, West Pasaman Regency. The type of research used is Qualitative Descriptive and field research , namely data collected directly by the author through structured interviews with the owner and employees of Desi Store. Data analysis used is SWOT analysis, namely analysis of data obtained to identify strengths, weaknesses, opportunities, and threats . The results of the study indicate that the SWOT analysis conducted indicates that Toko Desi's position is in Quadrant I (SO) with the highest score of 3.5, which means Toko Desi has excellent internal strengths and simultaneously faces various significant opportunities from the external environment. In conclusion, the SO strategy from a sharia perspective places Toko Desi in a strong position to grow aggressively while maintaining Islamic values. With consistent and innovative implementation, Toko Desi has the potential not only to increase sales volume but also to obtain blessings (barakah) in its business. The results of the overall analysis indicate that Toko Desi's promotional strategy is incomplete and still relies on traditional promotions. The IFE and EFE analyses prove that although there are many strengths and opportunities, weaknesses in the digital promotion aspect and threats from online competition need to be addressed immediately. Recommended promotional strategies include social media, digital training, event collaborations, and loyalty programs to increase sales sustainably and implement sharia marketing principles.